Zlomi stopalnic - Hari, Andrej (Medicinski razgledi, 2010)
Metatarsal fractures are relatively common and if malunited, they may be a frequent source of pain and disability. Nondisplaced fractures and fractures of the second to fourth metatarsal with displacement in the horizontal plane can be treated conservatively with protected weight bearing cast shoe for 4-6 weeks. In most displaced fractures, closed reduction can be achieved, but maintenance of the reduction needs internal fixation. Percutaneous pinning is suitable for most fractures of the lesser metatarsals. Intraarticular fractures, multiple fractures and open fractures frequently require open reduction and plate fixation. Transverse fractures at the metaphyseal-diaphyseal junction of the fifth metatarsal (Jones fractures) require an individual approach with respect to the level of activity and time to heal. Avulsion fractures of the fifth metatarsal bone are treated by open reduction and tension band wiring or screw fixation if displaced more than 2 mm or with more than 30% of the joint involved. The metatarsals are the most common site of stress fractures, most of which are treated conservatively. Symptomatic posttraumatic deformities need adequate correction, in most cases by osteotomy across the former fracture site.
Keywords: diagnostika; stopalo; poškodbe; zlomi; stopalnice; therapy; zdravljenje